1985
DOI: 10.1093/eurheartj/6.suppl_d.97
|View full text |Cite
|
Sign up to set email alerts
|

The Surdo-Cardiac Syndrome

Abstract: The first diagnosed cases of the surdo-cardiac syndrome are presented. The effect on the ECG of exercise, of digitalis treatment, of intramuscular injection of atropine and of intravenous injection of potassium chloride solution were studied. ECGs taken during attacks of syncope showed that the attacks are caused either by ventricular fibrillation or by ventricular standstill.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1988
1988
2002
2002

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Subsequently, Jervell and others reported the cases of five additional unrelated JLNS families from Norway [Jervell et al, 1966;Jervell and Sivertsen, 1967;Langslett and Sørland, 1975]. In 1964, Fraser et al, reported on six more families fulfilling the diagnostic Lisbeth Tranebjaerg, M.D., Ph.D., is professor of Medical Genetics at the University Hospital of Tromsø, Norway.…”
Section: Historical Perspectivementioning
confidence: 99%
“…Subsequently, Jervell and others reported the cases of five additional unrelated JLNS families from Norway [Jervell et al, 1966;Jervell and Sivertsen, 1967;Langslett and Sørland, 1975]. In 1964, Fraser et al, reported on six more families fulfilling the diagnostic Lisbeth Tranebjaerg, M.D., Ph.D., is professor of Medical Genetics at the University Hospital of Tromsø, Norway.…”
Section: Historical Perspectivementioning
confidence: 99%